Modification of contour planting system and its impact on improving infiltration characteristics of suboptimal land and soybean yields - Sunarti, Sunarti; Endriani, Endriani; Fuadi, Najla Anwar (Brawijaya University, 2026)
Low infiltration is one of the limiting factors on suboptimal land for agriculture. The infiltration is closely related to the soil's available water for plants. Low infiltration impacts soybean productivity. The contour planting system is a soil and water conservation technology that can be applied to increase infiltration. This research aimed to examine the impact of modifying the contour planting system on the infiltration characteristics of suboptimal land and soybean yields. The research used a quantitative approach with experimental methods (split-plot design) and three replications. The main plot treatment was the position of the land on the slope (the upper, middle, and lower). The subplot treatment was the contour planting system (standard contour planting system, 30o, 45o, and 60o from the contour line). Data were analyzed using analysis of variance and Duncan’s Multiple Range Test. The results showed that the modification of contour planting systems had no significant effect compared to the standard contour planting system in improving organic carbon content, bulk density, infiltration characteristics, and soybean plant height. The standard contour system resulted in higher soybean yields than the modification of the contour planting system. The position of the soil had a significant influence on soil properties, infiltration characteristics, plant height, and yields of soybeans. The soil characteristics, infiltration characteristics, and soybean yields resulting from standard and modification of contour planting systems showed suboptimal improvements. Therefore, further studies are needed to optimize the application of modification of contour planting systems to support the implementation of conservation agriculture systems.